The Disordered Mind : What Unusual Brains Tell Us About Ourselves - Kandel, Eric R. (New York Farrar, Straus and Giroux, 2018)
"Kandel ... confronts one of the most difficult questions we face: how does our mind, our individual sense of self, emerge from the physical matter of the brain? The brain's 86 billion neurons communicate with one another through very precise connections. But sometimes those connections are disrupted. The brain processes that give rise to our mind can become disordered, resulting in diseases such as autism, depression, schizophrenia, Parkinson's, addiction, and post-traumatic stress disorder. While these disruptions bring great suffering, they can also reveal the mysteries of how the brain produces our most fundamental experiences and capabilities--the very nature of what it means to be human"--
What brain disorders can tell us about ourselves -- Our intensely social nature : the autism spectrum -- Emotions and the integrity of the self : depression and bipolar disorder -- The ability to think and to make and carry out decisions : schizophrenia -- Memory, the storehouse of the self : dementia -- Our innate creativity : brain disorders and art -- Movement : Parkinson's and Huntington's diseases -- The interplay of conscious and unconscious emotion : anxiety, post-traumatic stress, and faulty decision-making -- The pleasure principle and freedom of choice: addictions -- Sexual differentiation of the brain and gender identity -- Consciousness : the great remaining mystery of the brain -- Coming full circle.
Includes bibliographical references and index.
Keywords: Mental illness -- Pathophysiology; Neuropsychiatry; Psychophysiology; Mental Disorders -- physiopathology; Neuropsychiatry -- methods; Mental Processes -- physiology; Psychophysiologic Disorders -- physiopathology